2012
DOI: 10.1002/ana.22686
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil protease inhibition reduces neuromyelitis optica–immunoglobulin G–induced damage in mouse brain

Abstract: Objective Neuromyelitis optica (NMO) is an inflammatory demyelinating disease of the central nervous system associated with pathogenic autoantibodies against the astrocyte water channel protein aquaporin-4 (AQP4). The presence of neutrophils is a characteristic feature in NMO lesions in humans. Neutrophils are not generally found in multiple sclerosis lesions. We evaluated the role of neutrophils in a mouse NMO model. Methods NMO lesions were produced in mice by intracerebral injection of immunoglobulin G (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
177
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(187 citation statements)
references
References 43 publications
7
177
2
1
Order By: Relevance
“…4B). Although inhibition of ELANE has been reported to ameliorate Th17-induced adoptive transfer EAE (24) and a mouse model of neuromyelitis optica (25), treatment with both inhibitors did not alter the development of actively induced EAE, indicating that both enzymes are not critically involved in neutrophil recruitment and effector function necessary for the development of actively induced EAE. Among other neutrophilproduced proinflammatory soluble factors, cytokines are good candidates as early signals setting up an inflammatory milieu.…”
Section: Cns-infiltrating Neutrophils Are a Source Of Cytokinesmentioning
confidence: 88%
“…4B). Although inhibition of ELANE has been reported to ameliorate Th17-induced adoptive transfer EAE (24) and a mouse model of neuromyelitis optica (25), treatment with both inhibitors did not alter the development of actively induced EAE, indicating that both enzymes are not critically involved in neutrophil recruitment and effector function necessary for the development of actively induced EAE. Among other neutrophilproduced proinflammatory soluble factors, cytokines are good candidates as early signals setting up an inflammatory milieu.…”
Section: Cns-infiltrating Neutrophils Are a Source Of Cytokinesmentioning
confidence: 88%
“…Prior passive-transfer mouse models of NMO involving intracerebral brain injection of NMO-IgG and complement produced NMO-like pathology, but without eosinophil infiltration (19,20). After testing multiple variations of existing models, including eotaxin and IL-5 infusion together with NMO-IgG and complement administration, we found that human-like NMO pathology could be produced by 3-day continuous intracerebral infusion of NMO-IgG and hc ( Figure 4A).…”
Section: Figurementioning
confidence: 91%
“…We reported recently that neutrophils and neutrophil elastase exacerbate NMO pathology in spinal cord slice cultures exposed to NMO-IgG and complement, and that the neutrophil elastase inhibitor Sivelestat largely prevented the neutrophil-dependent pathology (15). NMO pathology was greatly exacerbated in neutrophilic mice administered NMO-IgG and complement by intraparenchymal injection, and was reduced in neutropenic mice or in normal mice treated with neutrophil elastase inhibitors (20). A recent case report described rapid clinical deterioration in an NMO patient made neutrophilic by inadvertent administration of G-CSF (27).…”
Section: Figurementioning
confidence: 98%
See 1 more Smart Citation
“…Cinryze therapy was safe and associated with disability improvement to preattack levels in 9/10 patients after 1 month. Finally, inhibition of neutrophil elastase with sivelestat was beneficial in animal models of NMOSD [55,56], and a small open-label trial evaluating sivelestat for NMOSD attacks is currently being conducted in Japan.…”
Section: Treatment Of Nmosd Attacksmentioning
confidence: 99%